2024
DOI: 10.2147/jmdh.s435365
|View full text |Cite
|
Sign up to set email alerts
|

CA125-Associated Activated Partial Thromboplastin Time and Thrombin Time Decrease in Patients with Adenomyosis

Fanchun Yang,
Qingying Wang,
Rui Ma
et al.

Abstract: Adenomyosis patients are in a hypercoagulable state, and studies have shown that carbohydrate antigen125 (CA125) may relate to the hypercoagulability and thrombosis of patients with adenomyosis, but there is still a lack of clarity regarding the changes in CA125-related coagulation indicators. This study was to explore the changes and influencing factors of CA125-related coagulation parameters in patients with adenomyosis. Methods: Retrospective observational study conducted on 200 patients with adenomyosis (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The study conducted by Yang et al aimed to explore more deeply the changes and factors that influence the coagulation parameter, namely CA125, in patients with adenomyosis and obtained the results that CA125 levels in the adenomyosis group were significantly higher than in the leiomyoma group. 1 However, thrombin time was shorter in the adenomyosis group compared with the leiomyoma and control groups. The results obtained are in line with the objectives the author wants to achieve.…”
Section: Dear Editormentioning
confidence: 89%
See 2 more Smart Citations
“…The study conducted by Yang et al aimed to explore more deeply the changes and factors that influence the coagulation parameter, namely CA125, in patients with adenomyosis and obtained the results that CA125 levels in the adenomyosis group were significantly higher than in the leiomyoma group. 1 However, thrombin time was shorter in the adenomyosis group compared with the leiomyoma and control groups. The results obtained are in line with the objectives the author wants to achieve.…”
Section: Dear Editormentioning
confidence: 89%
“…In conclusion, we agree that the shortening of APTT and TT related to CA125 shows the importance of early detection of coagulation parameters in patients with elevated CA125 levels to determine hypercoagulability and prevent thrombi in adenomyosis. 1 However, several studies have found that CA-125 is not a strong enough predictor if stands alone in diagnostic screening, but it requires a combination of several biomarkers which also play a role in predicting and preventing thrombosis, therefore it is necessary to carry out further research with larger samples so that the results of this research will continue to develop. 2 …”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation